Reuse the Concrete Waste to Replace Coarse Aggregate: A Systematic Review: A systematic Review - Alafif, Eiad (Recent Trends in Civil Engineering and Built Environment, 2022)
The construction demolition wastes (CDW) are often costly and hazardous to the environment. Recycling this disposal will push the way towards sustainability and environmental conservation. The most suitable component of CDW for recycling purposes is concrete. This study reviews the previous founds in the utilization of waste concrete as coarse aggregates, often called recycle coarse aggregates (RCA), to be replaced with the natural course in several applications including concrete produces. Concrete that consists of recycled aggregate is often termed recycled aggregate concrete (RAC). It is essential to go through the common properties of recycled concrete, fresh and hardened, to promote and escalate its application in the local construction industry. This project research aims to review the significant factors that influence those properties including the replacement ratio and recent enhancing treatment methods to come up with greener recommendations for further improvements. Moreover, to highlight the most efficient uses regarding the recycled aggregate properties. Selected previously published founds in the Scopus database are reviewed and the results have been compared and analyzed for further discussion. High-level research techniques are used such as narrow-to-narrow limitations and systematic compartments to ensure the study outcomes quality. This study supports that the quality of recycled concrete is reduced with increasing RCA replacement ratio, but their overall performance is comparable to natural aggregate concrete (NAC). In addition, the recycled aggregate with the replacement ratio of 30% of RCA is similar to the control concrete in compressive strength quality. This research will encourage local studies for heading towards developing and facilitating this promised material.